2012
DOI: 10.1080/13691058.2012.723751
|View full text |Cite
|
Sign up to set email alerts
|

Let's talk about sex: reflections on conversations about love and sexuality in Kumasi and Endwa, Ghana

Abstract: This paper recounts and reflects on conversations about love and sexuality conducted with young people in Kumasi and Endwa, Ghana. It examines the settings of these conversations -in a kinship-based household, secondary schools and Pentecostal churches -and explores young people's reticence to talk about such matters in the light of intergenerational respect. Analysing young people's strategies of silence and provocative speech, the paper shows that, paradoxically, schools and churches provide institutionalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…(Jied, male, postgraduate) Questions raised by students suggested that they were unclear about sex between gay and lesbian couples -they wondered aloud about the physical aspects of same-sex relationships: reported a general silence around sex and sexuality in their society. Such reticence about sexual issues in different cultures is well documented (Bochow 2012;Griffiths et al 2008;Hyde et al 2010;Roudi-Fahimi and Feki 2011). In Khasi society, the silence around sexuality perhaps arises from cultural norms and is possibly aggravated by the lack of culturally acceptable words to discuss sexuality in public.…”
Section: Sin and Guiltmentioning
confidence: 90%
“…(Jied, male, postgraduate) Questions raised by students suggested that they were unclear about sex between gay and lesbian couples -they wondered aloud about the physical aspects of same-sex relationships: reported a general silence around sex and sexuality in their society. Such reticence about sexual issues in different cultures is well documented (Bochow 2012;Griffiths et al 2008;Hyde et al 2010;Roudi-Fahimi and Feki 2011). In Khasi society, the silence around sexuality perhaps arises from cultural norms and is possibly aggravated by the lack of culturally acceptable words to discuss sexuality in public.…”
Section: Sin and Guiltmentioning
confidence: 90%
“…It is commonly both an element in, and an expression of, inequalities in relationships between the young and old, between the genders, in general between those in power and those subservient to it. Secrecy bespeaks the inequalities in power and status that are engrained in kinship relations and may produce a sharpening of these inequalities (Bochow, 2012a). In that sense, knowing when and how to keep certain aspects of private lives and relationships a secret to others, becomes important in avoiding conflicts and tensions, and for ensuring that a good standing, public status and respect is being maintained for all parties involved.…”
Section: Introductionmentioning
confidence: 99%
“…Communication is a core skill running throughout this decision-making process—communicating with one's partner, family and friends, and a health care provider. In most parts of Nigeria, however, communicating about sex, fertility desires, and use of family planning methods is not culturally appropriate 29 , 30 . Furthermore, women and men often lack the skills they need to communicate effectively about such personal and sensitive subjects.…”
Section: Introductionmentioning
confidence: 99%